2014
DOI: 10.1149/2.0871414jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrowinning of Lithium from LiOH in Molten Chloride

Abstract: An investigation was carried out to determine the viability of electrowinning lithium from LiOH in molten chloride, with a view to developing a system for the storage and transportation of hydrogen using LiH as the storage medium. It was predicted from the chemical potential diagram for the Li-O-H system that Li metal cannot be electrowon from a LiOH-containing salt, as any Li generated by electrolysis will readily react with LiOH to form Li 2 O. Electrolysis in molten LiCl-42 mol% KCl or molten LiCl-17 mol% K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 9 publications
(10 reference statements)
0
29
0
Order By: Relevance
“…It has been pointed out lately that a critical challenge for Li-S batteries is achieving high energy density and high stability in a full cell with the use of a Li anode that is only 6 mA h cm −2 in size (~100% oversize) 38 . This is also of remarkable importance from a sustainability point of view, as the production of Li is environmentally unfriendly and expensive 39 . Until now, high energy density and stable cycling has not been achieved in a flexible Li-S full cell with a limited source of Li.…”
Section: Introductionmentioning
confidence: 99%
“…It has been pointed out lately that a critical challenge for Li-S batteries is achieving high energy density and high stability in a full cell with the use of a Li anode that is only 6 mA h cm −2 in size (~100% oversize) 38 . This is also of remarkable importance from a sustainability point of view, as the production of Li is environmentally unfriendly and expensive 39 . Until now, high energy density and stable cycling has not been achieved in a flexible Li-S full cell with a limited source of Li.…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuations in the price of metallic lithium create cost issues for Li-metal batteries. [49] In anode-free configuration, the minimum amount of Li required for operation is stored inside the cathode, which can be produced using lithium compounds such as Li 2 CO 3 or LiOH, whereas metallic Li anodes require much higher purity (e.g., by energy-intensive electrolysis [50] ). Based on the cost model of Schmuch et al [41] anode material costs amount to approximately 20% in the case of LIB, and 33-57% in the case of LMSSB (N/P = 3).…”
Section: Manufacturing and Costsmentioning
confidence: 99%
“…This uses up some of the electric currents, which leads to a decreased current efficiency as suggested by Laude et al 25 The current efficiencies in the electrolysis of LiOH were reported to range from 38% 25 up to >80%. 26,27 Given the nature of such reactions discussed in this section, it is concluded that such a pathway that starts with lithium metal and undergoes a regeneration cycle for continuous operation in an LNG plant is theoretically possible with attention to the highlighted details and the concerning reaction conditions. Some of these conditions include temperature, pressure, and energy requirements.…”
Section: Electrolysis Of Lithium Hydroxidementioning
confidence: 99%